LENGTH-WEIGHT RELATIONSHIP OF GOLDEN MAHSEER : TOR PUTITORA (HAMILTON) FROM RANJIT SAGAR RESERVOIR - SINGH, RAJINDER; SHAFIQ, MEDIHA (Journal of the Inland Fisheries Society of India, 2022)
Studies on the length-weight relationship in fishes have been recognized as important aspect in fishery biology and are conducted primarily tofacilitate the conversion of one measurement into another in order to have an assessment of growth rate of the fish crop. Such relationship not onlyhelps in determining the fluctuations within the population of different localities (LeCren, 1951) and variations in the expected weight due to changein wellbeing during the life cycle of fish but, also finds tremendous utility in fishery management (Gaur and Pathani, 2005).